Acute Biliary Pancreatitis is Associated With Adverse Outcomes in the Elderly: A Propensity Score–Matched Analysis. Issue 7 (August 2019) - Patel, Kishan; Li, Feng; Luthra, Anjuli; Hinton, Alice; Lara, Luis; Groce, Royce; Hosmer, Amy; McCarthy, Sean T.; Strobel, Sebastian; Conwell, Darwin L.; Krishna, Somashekar G.
Abstract : Goals and Background: In the elderly (age, 65 y or older), acute pancreatitis is most frequently because of gallstones; however, there is a paucity of national estimates evaluating outcomes of acute biliary pancreatitis (ABP). Hence, we utilized a representative population database to evaluate the outcomes of ABP among the elderly. Study: The National Readmission Database provides longitudinal follow-up of inpatients for 1 calendar-year. All adult inpatients (18 y or older) with an index primary admission for ABP between 2011 and 2014 were evaluated for clinical outcomes of mortality, severe acute pancreatitis (SAP), and 30-day readmission. Outcomes between age groups (≥65 vs. <65 y) were compared using multivariate and one-to-one propensity score–matched analyses. Results: Among 184, 763 ABP admissions, 41% were elderly. Index mortality and SAP rates in the elderly were 1.96% and 21.5%, respectively. Elderly patients underwent more ERCPs (27.5% vs. 23.6%; P <0.001) and less frequent cholecystectomies (44.4% vs. 58.7%; P <0.001). Elderly patients had increased odds of mortality and SAP along with an age-dependent increase in the odds of adverse outcomes; patients aged 85 years or older demonstrated the highest odds of SAP [odds ratio (OR), 1.3; 95% confidence interval (CI): 1.2, 1.4] and mortality (OR, 2.2; 95% CI: 1.7, 2.9) within in the elderly cohort. Propensity score–matched analysis substantiated that mortality (OR, 2.8; 95% CI: 2.2, 3.5) and SAP (OR, 1.2; 95% CI: 1.1, 1.3) were increased in the elderly. Conclusions: Current national survey reveals adverse clinical outcomes among elderly patients hospitalized with ABP. Consequently, there is a need for effective management strategies for this demographic as the aging population is increasing nationally. Abstract : Supplemental Digital Content is available in the text.